2012
DOI: 10.1021/jo300373m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Optical Properties of 4H-Pyran-4-ylidene Donor-Based Chromophores: The Relevance of the Location of a Thiophene Ring in the Spacer

Abstract: A series of new 4H-pyran-4-ylidene donor-based chromophores with a thiophene ring in the spacer has been synthesized. The linear and nonlinear optical (NLO) properties of these compounds have been determined and compared with the results of computational calculations. The position of the thiophene ring proved essential to optimize the figure of merit μβ, with the best results obtained when the heterocyclic system was closer to the donor moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…It is calculated as the difference of average C-C single and double bonds. 54,91 It is noted that compound 4 has the largest Dr value, while compound 7 has the smallest Dr value for all the states. This may occur because of large dihedral angles between adjacent repeating units leading to poor conjugation in pentamer 4, and the highly conjugated planar structure of pentamer 7.…”
Section: A Comparison Of Geometries Of the Doped Oligomers With Their...mentioning
confidence: 98%
“…It is calculated as the difference of average C-C single and double bonds. 54,91 It is noted that compound 4 has the largest Dr value, while compound 7 has the smallest Dr value for all the states. This may occur because of large dihedral angles between adjacent repeating units leading to poor conjugation in pentamer 4, and the highly conjugated planar structure of pentamer 7.…”
Section: A Comparison Of Geometries Of the Doped Oligomers With Their...mentioning
confidence: 98%
“…26,[33][34][35] γ-methylenepyran compounds are organic chromophores which have been recently integrated as donors in push-pull devices for applications in non-linear optics and photovoltaic cells. [36][37][38][39] Interestingly, electrochemical studies have shown that methylenepyran compounds can undergo fast dimerization by σ C−C bond making upon oxidation at moderate potential values (E p ~ 0.3 V vs. Fc) in organic solvents. 37,38,40,41 The resulting bispyrylium species is reduced irreversibly around −0.8 V vs. Fc leading back to the initial methylenepyran by C−C bond breaking (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Figure 3, Mulliken population analysis confirms these trends indicating a negative charge over the acceptor group (-0.569 e in 1 and -0.534 e in 2) which is around 2 times higher than the sum of the positive charge over the two TPA donor groups (+0.260 e in 1 and +0.258 e in 2), while the π-spacer is largely polarized bearing around 70% (+0.310 e in 1 and +0.276 e in 2) of the total positive charge. Moreover, it is worth highlighting that the positive charge located in the pyran ring (together with vinyl unit) is of the same order 35 or even larger 36,37 to those encountered for other D--A derivatives with the 4H-pyranylidene as main donor. Thus, these data account for a significant polarization of the -conjugated structure in these V-shaped chromophores.…”
Section: Synthesismentioning
confidence: 78%